Analysis of Demographics to Quality of CIO, Ethical Climate, Level of Ethics and Integrity and Organizational Commitment in the Malaysia Public Sector - Asmawati, Sajari; Hasnah, Haron; Ishak, Ismail (Universiti Malaysia Pahang, 2018)
This paper provides a descriptive analysis of climate, quality of CIO and organizational commitment in the public sector. Age, gender, educational level, having a professional certificate and heading the integrity unit are the demographics variables examined in this study. These variables, using chi square analysis were examine to see if they have a significant relationship with ethical climate, organizational commitment and quality of CIO. It was found that age (younger), gender (female) as integrity officers were significantly related to organizational commitment. Head of integrity units were also found significant to be a quality CIO as compared to integrity officers who are not heading a unit. However, none of the demographics variables were found to have a significant relationship with ethical climate. It is recommended that the public sector need to retain older officers and recruit female integrity officers if they would like their integrity officers to stay longer in the organization. Another recommendation is to have a CIO who heads the integrity units rather than not heading one as they portray a higher competence, independence and perform work as required of them.